Influence of Poultry Farmers Coping Strategies of High Cost of Feed on Food Security Status in South-west Nigeria - Afodu, O.; Balogun, O.; Afolami, C.; Akinboye, O.; Akintunde, A.; Ayo-Bello, T.; Ndubuisi-Ogbonna, L.; Shobo, B.; Adefelu, A. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2022)
Poultry products have served as one of the cheapest protein source in the Nigeria today making it one of the food ingredients to fight protein malnutrition in the Nigeria economy. The poultry industry also provides a means of living for the Nigerian populace. Recently the poultry industry is facing a serious decline due to the high cost of feed which consist about 75% of total cost of production. This research was conducted to determine the influence of poultry farmers coping strategies of high cost of feed on their food security status in South-West Nigeria. The study population consist of registered poultry farmers with the Poultry Association of Nigeria (PAN) in the study area. This study adopted a multi-stage sampling technique to select 575 poultry farmers; though only 515 questionnaires were fitted for the study. Descriptive and inferential statistics were used for data analysis. The food security status was captured with the use of Household Food Insecurity Access Scale, while Logit regression was used to analyse the effect of coping strategies of high cost of price of feed on food security status among the poultry farmers. Majority (56.9%) of the poultry farmers were male. Majority of the poultry farmers were found to be young and active with about 81% of them were between the age range of 20 -50 years. A large number of them (45.4%) were found to be severe food insecure. The coping strategies adopted include zero response, use of compounded feed, use of integrated farming, reduce flock size and exiting the poultry business. Access to credit and number of coping strategies adopted were the major variables influencing the food security status of the poultry farmers during the period of high cost of feed.